Peran dan Kontribusi Syehk Fattah Rahmatullah dalam Mengembangkan Dakwah Islam di Semarang Garut pada Abad ke XVI - muhamad rafly Gunatama; Agus Permana (Universitas Negeri Makassar, 2022)
A This research article aims to (1) find out the history of curriculum vitae about who a muslim figure or ulama cleric named Syeikh Fatah Rahmatullah the life in Samarang Garut in the 15th century (2) for find out role/contribution of yeikh Fatah Rahmatullah in developing Islamic da’wah in Samarang Garut in the 15th century (3) to find out what are thr relics Sheikh Fatah Rahmatullah. Sheikh Fatah Rahmatullah is the son of Sembah Dalem Sewa Sagara and grandson of SunanTubuy and also a great scholar who onces lived in Samarang Garut sub district right in Tanjung Singuru Village, Sheikh Fatah Rahmatullah who lived in the 15th century was actually not a native of Samarang Garut, but Islamic fighters and students who were sent by Sultan Hasanudin form Banten to spread islam to the local community in Samarang Garut, precisely in Tanjung Singuru Village. Sheikh Fatah when leading da’wah is very intelligent and humble in preaching. Sheikh Fatah when he was sent to Samarang Garut acted as a cleric and contribution to estabilishing a boarding school in his preaching namely Tanjung Singuru Islamic boarding school.But this pesantren Tanjung Singru is thougt to have survived only until the mid-17th century when Sheikh Fatah had been living for a long time. Keywords : Sheikh Fatah Rahmatullah; Role/Contribution; Curriculum Vitae